Evaluating the impact of curriculum infusion on US college students' alcohol use and academic performance. (October 2016) - Samuolis, Jessica; Lazowski, Andrew; Kessler, Janice
Objectives: This paper explores the extent to which curriculum infusion (CI) impacted undergraduate students' alcohol use, perceived peer alcohol use, use of protective behavioural strategies, academic performance and course engagement. Design: Two faculty members infused content on norms and protective behavioural strategies into selected academic courses. Setting: This study was conducted in a small liberal arts university in the northeastern part of the USA. Methods: A sample of 215 undergraduates from research design and statistics courses in the fall semester of 2013 and the spring and fall semesters of 2014 were selected. CI was experienced by 100 students and 115 students comprised the comparison group. Surveys were distributed at the end of each semester to these selected groups and the results were analysed. Results: Students who witnessed CI showed no improvement in alcohol use outcomes; however, there was a trend level effect for frequency of use. CI students reported higher expected final grades and similar levels of course engagement to comparison group students. Conclusion: CI is a topic that requires in-depth scientific research to assess its value on positively affecting college drinking consequences. From a pedagogical standpoint, CI was successful since it did not negatively impact on students' engagement and it was associated with higher expected final grades.